2019
DOI: 10.3390/condmat4020060
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Romans’ Route to Charge Density Waves in Cuprates

Abstract: An account is given of the main steps that led the research group in Rome, to which the author belongs, to the formulation of the charge-density-wave scenario for high- T c superconducting cuprates. The early finding of the generic tendency of strongly correlated electron systems with short range interactions to undergo electron phase separation was subsequently contrasted with the homogenizing effect of the long-range Coulomb interaction. The two effects can find a compromise in the formation of incomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…Finally, we have reported new information on the quantum complex scenario near criticality in nickelates which opens new venues to applications and developments of new magnetic and electronic devices. In fact, in the proximity of a topological Lifshitz transition it is possible to control novel macroscopic functionalities by a weak external stimulus such as stress [25][26][27][28][29][30][31][32][33][34][35][36][71][72][73][74][75], current density [64,65] or photon illumination dose [5,[76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have reported new information on the quantum complex scenario near criticality in nickelates which opens new venues to applications and developments of new magnetic and electronic devices. In fact, in the proximity of a topological Lifshitz transition it is possible to control novel macroscopic functionalities by a weak external stimulus such as stress [25][26][27][28][29][30][31][32][33][34][35][36][71][72][73][74][75], current density [64,65] or photon illumination dose [5,[76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…At Superstripes 2019 Tsuchiya et al [87] and Nakagawa et al, [88] have reported the most recent results on the investigation of carrier dynamics and phase separation by spectrally resolved pump-probe spectroscopy and polarized time-resolved spectroscopy of electronic phase separation. Arrested nanoscale phase separation was predicted for multiband correlated metals near a topological Lifshitz transition [89] which is reached by tuning strain and charge [90] with a complex landscape of polaronic short range charge density waves [91].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 99%
“…A special case of the Hamiltonian Equation (1) is realized by the steep band/flat band scenario [11][12][13][14][15][16][55][56][57][58][59][60][61]. This corresponds to a band with itinerant Fermi liquid type character and a localized dispersion-less polaronic one [5][6][7][8]30,[62][63][64][65][66][67]…”
Section: The Steep Band/flat Band Modelmentioning
confidence: 99%